Quantitative risk evaluation based on IEC 61508 for SW functional safety of marine bigdata analysis system - Yeong Kim, Hee (International Journal of Engineering and Technology, 2018)
Background/Objectives: SW functional safety is beyond the SW quality and IEC 61508 is needed instead of ISO/IEC 9126.Embedded SW for Sensor or actuation is needed to be tested as perspectives of functional safety.Methods/Statistical analysis: Risk analysis and quantitative risk evaluation procedure is used for estimating the risk of SW related to safety of equipment and embedded system. FMEDA (Failure Mode, Effects and Diagnostic Analysis) is one of the method for certifying SIL(Safety Integrity Level) but it is not easy to use when the sensors or actuations are too many. FMEA (Failure Mode and Effects Analysis) is simple method to use with another bigdata analysis technique. MBAS (Marine Bigdata Analysis System) is the SW to be analyzed the risk quantitatively in this study to assure the target safety.Findings: Test methods based on IEC 61508-3 are defined as SIL to assure SW quality effectively but SIL of FMEDA uses complex equations to be defined and sensing equipment parts could be classified as failure rates for input data for equations. I recommend simple method to decide test methods as Severity Level that is very similar to SIL but very easy based on FMEA in this study. MBAS is bigdata solution and sensing data can be validated and verified by the analyzed results of the relation of process functions as dependent value from sensor data as independent value.Improvements/Applications: No needed to be classified and be calculated the detected or undetected failure rate of sensor to assign the parts of equipment to define risks.Â